Exploring self and society - Billington, Rosamund (Macmillan, 1998)
This text addresses contemporary society in an immediate and thought-provoking manner and will be a timely and topical introduction to the dynamic and critical dimensions of sociology. It adopts a broad social science approach which reflects both the authors' competencies and also the widening and overlaying boundaries of the social sciences. Starting with the problem-oriented agenda of the social sciences, it explores the tensions between structure, agency and process via the idea of a structure-bound and yet creative and participatory self.